2021
DOI: 10.3390/ph14101004
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-Lowering Bioactivity of Microalga Nitzschia laevis Extract Containing Fucoxanthin in Murine Model and Carcinomic Hepatocytes

Abstract: Non-alcoholic fatty liver disease (NAFLD), characterized by hepatic steatosis, is one of the most common liver diseases worldwide. So far, no definitive medical treatment has been established to treat NAFLD except for lifestyle medication. Nitzschia laevis extract (NLE), a microalgal extract rich in fucoxanthin, has been previously demonstrated to reduce bodyweight in high-fat-diet (HFD) C57BL/6J mice, indicating potential for prevention of NAFLD. In the present study, we investigated the lipid-lowering effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…Hyperlipidemia easily leads to serious metabolic diseases, which credits to a higher TG, TC, LDL and/or lower HDL concentration in the serum. The current results showed significant increase of TG, TC, LDL and decreased of HDL in HFD-induced group, while fucoxanthin supplementation for 8 weeks largely reversed them (Table 1), which agrees with our previous report [19] . However, a dose-dependent effect of fucoxanthin was observed for TG and HDL, but not TC and LDL, which reminds that dosage effects should be carefully considered when supplied with fucoxanthin.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Hyperlipidemia easily leads to serious metabolic diseases, which credits to a higher TG, TC, LDL and/or lower HDL concentration in the serum. The current results showed significant increase of TG, TC, LDL and decreased of HDL in HFD-induced group, while fucoxanthin supplementation for 8 weeks largely reversed them (Table 1), which agrees with our previous report [19] . However, a dose-dependent effect of fucoxanthin was observed for TG and HDL, but not TC and LDL, which reminds that dosage effects should be carefully considered when supplied with fucoxanthin.…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, both the histological and physiological results indicated reduced lipid accumulation by fucoxanthin (Fig. 2), which was in line with previous studies [19,24] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The experimental results showed that NLE significantly reduced body weight and hepatic steatosis and inhibited cellular lipid accumulation in mice, and NLE also achieved lipid-lowering effects by enhancing hepatic mitochondrial functions, such as increasing the oxygen consumption rate and mitochondrial membrane potential, as well as inhibiting fatty acid synthesis. Therefore, it is an extremely promising natural product for the prevention of NAFLD [69]. The chemical structures of compounds 16-22 are shown in Figure 6.…”
Section: Nafldmentioning
confidence: 99%
“…These results are consistent with those of Jeon et al, who showed that a microalgal extract from Nitzschia laevis rich in fucoxanthin significantly reduced inguinal fats and attenuated hepatic steatosis in HFD-fed mice. This was highly attributed to its ability to improve hepatic mitochondrial functions, as indicated by enhanced oxygen consumption rate (OCR), mitochondrial membrane potential (MMP), and inhibited fatty acid production via phosphorylation of acetyl-CoA carboxylase (ACC) . A fucoxanthin-rich extract from Undaria pinnatifida markedly suppressed hepatic lipid levels in DIO mice, which was correlated with decreased activities of enzymes involved in fatty acid synthesis, including FAS, ME, and G6PD, along with increased fatty acid oxidation in the liver .…”
Section: Brown Algae and Its Bioactive Compoundsmentioning
confidence: 99%